2014
DOI: 10.1055/s-0034-1377332
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effect of Pharmacotherapy in Common Cold/Acute Bronchitis – the Bronchitis Severity Scale (BSS)

Abstract: The validated BSS appears to be a reliable tool to assess therapeutic effects in CC/AB. The BSS and its subscales are recommended as outcome measures for future drug trials in CC/AB, but also help physicians to focus their consultation in patients with CC/AB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 29 publications
1
32
0
8
Order By: Relevance
“…In AB, the Bronchitis Severity Scale (BSS) [32][33][34] included intensity ratings of the symptoms coughing, sputum production, rales/rhonchi at auscultation, chest pain during coughing, and dyspnea. In children aged 6years and younger, sputum production and chest pain during coughing could not be reliably assessed and were thus omitted from the calculation of the BSS total score.…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…In AB, the Bronchitis Severity Scale (BSS) [32][33][34] included intensity ratings of the symptoms coughing, sputum production, rales/rhonchi at auscultation, chest pain during coughing, and dyspnea. In children aged 6years and younger, sputum production and chest pain during coughing could not be reliably assessed and were thus omitted from the calculation of the BSS total score.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…In AB, symptom severity was assessed in all trials using the BSS as a validated scale 33,34 which has been shown to discriminate reliably between manifestations of bronchitis of different severities. 32 Although in ARS and ATP no formal validations for the available scores have been published so far, our review demonstrates that the results obtained with the SSS and the TSS showed a high degree of concordance with other symptom related efficacy measures like the IMOS (as a global rating of clinical outcome), time until the onset of a meaningful treatment effect, and the ability to go to work or attend school or kindergarten.…”
Section: Ulbricht Et Almentioning
confidence: 99%
“…Many patented herbal remedies are available for trials and treatment. Moreover, for acute bronchitis/common cold, a 15 years old tool, BSS (bronchitis severity scale) is now a validated outcome measure [31,32]. Also recommendations for cough monitoring now exist [10].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…ввели цей термін у наукову літературу, і з того часу він зустрічається в багатьох публікаціях. У 2013 році був опублікова-ний системний аналітичний огляд досліджень, у яких використовували шкалу BSS [9,10]. Практич-но всі наведені дослідження та масштабний Кокра-нівський метааналіз демонструють, що ця проста шкала є об'єктивним інструментом як для загаль-ної оцінки регресу симптомів гострого бронхіту за певний період часу (початковий, під час лікування та після його закінчення), так і для аналізу окремих підрозділів: «кашель» і «мокротиння» [11].…”
Section: результати та обговоренняunclassified